A teoria da Ação Social de W.E.B. Du Bois: a mensagem negra-africana que surge do "acaso" - Elioterio dos Santos, Hasani (2024)
This dissertation presents an analysis of W.E.B. Du Bois’s social action theory, which was developed from the end of the 19th century. The study is methodologically close to Gilroy (1993) and Appiah (2014), interpreting Du Bois as part of a “line of descent” from black and African counterculture in modernity. From this, the argument is that Du Bois’s social action theory is different from the classical sociological tradition. Part of the analytical effort of this study, therefore, is the exercise of contrast between sociological theories of modernity and what Gikandi (2005) and Gooding-Williams (2009) classified as “Duboisian modernism”. It appears that theories of modernity explain human actions considering the process of rationalization of the world, interest, econometric motivation, and/or search for integration and social mobility. Du Bois’s social action theory, instead, is based on the principle of “chance” - historical processes that were not predicted, expected, or desired by the actors, such as colonization and the division of the world into racial groups. The study empirically uses a selection of texts written by Du Bois between 1930 and 1947, on Black Cooperativism and Pan-Africanism, which reinforce this interpretation of his social action theory and reconstruct the assumptions of Cultural, Post-Colonial, and African Diaspora Studies.